New Approaches in Government Budgeting - بیت المال, محمد (Dirasat in Economics and Business, 1981)
The limitations and shortcomings of the traditional system of budgeting is being widely recognized by developed countries because it is no longer considered as an effective planning device. And because it emphasizes the financial control function, it has a limited value as a source of information to the decision-makers. As a response to these limitations, attempts have been made to overcome them and to make the budget an effective planning device for better resource allocation. Performance budgeting, Planning-ProgrammingBudgeting System (PPBS), Zero-Base Bud-geting, and Management By Objectives (MBO) have been considered as major reforms to improve the budget process. The purpose of this article is to present these new developments to the Arab readers with an emphasis on PPBS because of its segnificance. Although the PPBS system was not successful in some cases, it has potential for improving the process of resource allocation as the experience of the U.S. Department of Defence with PPBS has shown.